2013
DOI: 10.1093/mp/sst099
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule Depolymerization Affects Endocytosis and Exocytosis in the Tip and Influences Endosome Movement in Tobacco Pollen Tubes

Abstract: Polarized organization of the cytoplasm of growing pollen tubes is maintained by coordinated function of actin filaments (AFs) and microtubules (MTs). AFs convey post-Golgi secretory vesicles to the tip where some fuse with specific domains of the plasma membrane (PM). Secretory activity is balanced by PM retrieval that maintains cell membrane economy and regulates the polarized composition of the PM, by dividing lipids/proteins between the shank and the tip. Although AFs play a key role in PM internalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 80 publications
5
64
0
Order By: Relevance
“…4). The small area of NtEXO70A1a localization corresponds to the previously described area of exocytosis maximum in the pollen tube (Bove et al, 2008;Idilli et al, 2013;Luo et al, 2016). This localization is in accordance with previous characterizations of Arabidopsis EXO70A1 as the isoform generally responsible for exocytosis in many plant tissues (Synek et al, 2006;Hála et al, 2008;Samuel et al, 2009;Kulich et al, 2010;Drdová et al, 2013;Fendrych et al, 2013;Zhang et al, 2016;Vukašinovi c et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…4). The small area of NtEXO70A1a localization corresponds to the previously described area of exocytosis maximum in the pollen tube (Bove et al, 2008;Idilli et al, 2013;Luo et al, 2016). This localization is in accordance with previous characterizations of Arabidopsis EXO70A1 as the isoform generally responsible for exocytosis in many plant tissues (Synek et al, 2006;Hála et al, 2008;Samuel et al, 2009;Kulich et al, 2010;Drdová et al, 2013;Fendrych et al, 2013;Zhang et al, 2016;Vukašinovi c et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Alternatively, there can be two subpopulations of NtSEC3a-containing exocyst particles: one binding NtEXO70A1a and the other binding NtEXO70B1. This would also explain why the previously described membrane signal of NtSEC3a (Bloch et al, 2016) seems rather broad in comparison with the narrow area of bulk exocytosis in the tobacco pollen tube (Bove et al, 2008;Idilli et al, 2013;Luo et al, 2016). Second, NtEXO70B1 also could play a role in pollen tube endocytosis.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Conversely, based on colabeling with FM1-43 and FM4-64, it was concluded that exocytosis takes place in a subapical collar located in the transition zone between the tip and the shank, as well as at the shank, but not at the tip (Bove et al, 2008;Zonia and Munnik, 2008). In agreement, the pollen tube-specific syntaxin GFP-SYP124 was observed in the inverted cone, 10 to 25 mm away from the tip (Silva et al, 2010), and fluorescence recovery after photobleaching experiments with FM dyes also have indicated that exocytosis takes place at the subapical region (Bove et al, 2008;Moscatelli et al, 2012;Idilli et al, 2013). Yet, based on pollen tube reorientation experiments in a microfluidics device, it was concluded that growth takes place at the tip rather than at a subapical collar located in the transition zone between the apex and the shank (Sanati Nezhad et al, 2014).…”
mentioning
confidence: 72%
“…In tip-growing cells, MTs reside on the cell cortex in a generally longitudinal orientation and contribute to tip growth. In many angiosperm pollen tubes, disruption of the MTs has no apparent effect on growth (Cai and Cresti, 2010), but it has recently been reported to affect both endocytosis and exocytosis in the tip of tobacco (Nicotiana tabacum) pollen tubes (Idilli et al, 2013). The growth of gymnosperm pollen tubes is inhibited by MT-depolymerizing drugs (Anderhag et al, 2000;Justus et al, 2004).…”
Section: Introductionmentioning
confidence: 99%